In vitro activity of eravacycline and comparator agents against bacterial pathogens isolated from patients with cancer. Issue 2 (2nd March 2023) - Rolston, Kenneth; Gerges, Bahgat; Nesher, Lior; Shelburne, Samuel A; Prince, Randall; Raad, Issam
Abstract: Background: Bacterial infections are common in patients with cancer, and many bacteria have developed resistance to currently used antibiotics. Objectives: We evaluated the in vitro activity of eravacycline (a recently developed fluorocycline) and comparators against bacterial pathogens isolated from patients with cancer. Methods: Antimicrobial susceptibility testing was performed using CLSI-approved methodology and interpretive criteria for 255 Gram-positive and 310 Gram-negative bacteria. MIC and susceptibility percentage were calculated according to CLSI and FDA breakpoints when available. Results: Eravacycline had potent activity against most Gram-positive bacteria, including MRSA. Of 80 Gram-positive isolates with available breakpoints, 74 (92.5%) were susceptible to eravacycline. Eravacycline had potent activity against most Enterobacterales, including ESBL-producing organisms. Of 230 Gram-negative isolates with available breakpoints, 201 (87.4%) were susceptible to eravacycline. Eravacycline had the best activity among comparators against carbapenem-resistant Enterobacterales, with 83% susceptibility. Eravacycline was also active against many non-fermenting Gram-negative bacteria, with the lowest MIC90 value among comparators. Conclusions: Eravacycline was active against many clinically significant bacteria isolated from patients with cancer, including MRSA, carbapenem-resistant Enterobacterales, and non-fermenting Gram-negative bacilli. Eravacycline might play an important role in the treatment of bacterial infections in patients with cancer, and additional clinical evaluation is warranted.